Price Competition and Market Concentration: An Experimental Study - Martin Dufwenberg; Uri Gneezy (Uppsala University, Department of Economics, 1998)
The classical price competition model (named after Bertrand), prescribes that in equilibrium prices are equal to marginal costs. Moreover, prices do not depend on the number of competitors. Since this outcome is not in line with real-life observations, it is known as the Bertrand Paradox. Many theoretical problems with the original model have been considered as an explanation of the paradox in the literature. In this paper we experimentally investigate a model which is immune to the theoretical critique of the original model. We find, nevertheless, that the outcome does depend on the number of competitors: the Bertrand solution does not predict well when the number of competitors is two, but after some opportunities for learning are provided it tends to predict well when the number of competitors is three or four. A bounded rationality explanation of this is suggested.
urn:nbn:se:uu:diva-2414
Keywords: C90; D43; 330; Price competition; Bertrand model; market concentration; experiment; learning